2021
DOI: 10.1371/journal.pone.0247592
|View full text |Cite
|
Sign up to set email alerts
|

A knowledge-based multivariate statistical method for examining gene-brain-behavioral/cognitive relationships: Imaging genetics generalized structured component analysis

Abstract: With advances in neuroimaging and genetics, imaging genetics is a naturally emerging field that combines genetic and neuroimaging data with behavioral or cognitive outcomes to examine genetic influence on altered brain functions associated with behavioral or cognitive variation. We propose a statistical approach, termed imaging genetics generalized structured component analysis (IG-GSCA), which allows researchers to investigate such gene-brain-behavior/cognitive associations, taking into account well-documente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 100 publications
(131 reference statements)
1
1
0
Order By: Relevance
“…The regression method (Thomson, 1934) was used for the estimation of factor scores. We confirmed that our MATLAB code for GSCA and PLSPM produced the same solutions as GSCA Pro (version 1.1.4) (Hwang, Cho, & Choo, 2021a) and SmartPLS 3.0 (Ringle, Wende, & Becker, 2015). The maximum number of iterations was set to 10,000 for all SEM approaches.…”
Section: Design and Model Estimationsupporting
confidence: 59%
See 1 more Smart Citation
“…The regression method (Thomson, 1934) was used for the estimation of factor scores. We confirmed that our MATLAB code for GSCA and PLSPM produced the same solutions as GSCA Pro (version 1.1.4) (Hwang, Cho, & Choo, 2021a) and SmartPLS 3.0 (Ringle, Wende, & Becker, 2015). The maximum number of iterations was set to 10,000 for all SEM approaches.…”
Section: Design and Model Estimationsupporting
confidence: 59%
“…Furthermore, we showed that in its most general form, the GSCA model is not a structural model but an index‐generating model using certain rules, given the covariance matrix of indicators. Under this index‐generating model, GSCA can be seen as a statistical approach for creating composite indexes and testing their relationships with other variables based on prior knowledge (Hwang, Cho, Jin, et al., 2021). From this modelling perspective, a component is no longer an independent entity that causes other variables to vary at the population level, simply corresponding to a composite index of indicators derived based on a given theory‐driven model.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…While GSCA is a relatively recent approach compared to other SEM techniques, it has gained acceptance and recognition within the research community. It has been successfully applied in various fields, including social sciences, business, and psychology, to examine complex relationships and identify latent constructs (Hwang & Takane, 2014;Hwang et al, 2021;Jung et al, 2021).…”
Section: Discussionmentioning
confidence: 99%